79 Effects of dietary net energy and neutral detergent fiber levels on growth performance and carcass characteristics of growing finishing pigs. (30th November 2020) - Lu, Ning; Vier, Carine; Cast, Wayne; Orlando, Uislei; Gonçalves, Márcio; Zhou, Xun; Young, Malachy
Abstract: Our objective was to determine the effects of feeding different net energy (NE) and neutral detergent fiber (NDF) on performance of growing-finishing pigs from 30- to 135-kg. A total of 2, 058 barrows and gilts (PIC 380×Camborough, initial BW 33.4±0.60 kg) were used in a 97-d growth trial with 21 pigs per pen and 14 pens per treatment in a randomized complete block design. Treatments were formulated to contain 2.11, 2.21, 2.32, 2.42, 2.53, 2.63, and 2.73 Mcal NE/kg; and 24.2, 19.7, 15.1, 10.6, 10.2, 9.8, and 9.5% NDF throughout the experiment. Wheat, wheat byproducts, barley, rye, peas, fababeans, and canola oil were used with NRC (2012) loading values to achieve the treatments. Dietary lysine levels were set to meet PIC2016 lysine requirements for finishing gilts. Experimental data were analyzed using generalized linear mixed models and linear and quadratic polynomial contrasts were built with pen as the experimental unit. Increasing NE or decreasing NDF improved (linear and quadratic, P< 0.05) average daily gain (ADG), gain-to-feed ratio (G:F), carcass ADG, and carcass G:F (Table 1); but reduced (linear and quadratic, P< 0.05) average daily feed intake (ADFI). Comparing to pigs fed 2.42 Mcal/kg diet (energy equivalent to a corn-soybean meal diet), even though those fed 2.11 Mcal/kg diet had 8.7% increment on ADFI, daily NE intake was still 5.4% less. Hot carcass weight, backfat depth, and carcass yield increased (linear and quadratic, P< 0.05) and lean yield decreased (linear and quadratic, P< 0.05) with increasing dietary NE and decreasing NDF. No evidence for differences (P >0.10) were observed for loin depth. Removal and mortality rate was reduced (quadratic, P< 0.05) with increasing dietary NE and decreasing dietary NDF. In summary, increasing dietary NE while reducing dietary NDF resulted in improvements on growth performance, carcass characteristics, and removal and mortality rate.